Maternal Smoking and Hospital Treatment During Pregnancy. Issue 7 (16th August 2019) - Wallin, Hanna P; Gissler, Mika; Korhonen, Päivi E; Ekblad, Mikael O
Abstract: Introduction: Previous research suggests that young maternal age, smoking, hospitalization during a previous pregnancy, and poor self-rated health could be risk factors for prenatal hospitalization. Methods: The objective of this retrospective observational register study was to investigate if maternal smoking during pregnancy is associated with mother's need for hospital treatment during pregnancy. The study population consists of all singleton pregnancies ( n = 961 127) in 1999–2015 in Finland. Information on maternal smoking was received from the Medical Birth Register in three classes: nonsmoker, quit smoking in the first trimester, and continued smoking throughout the pregnancy. These data were linked with the Hospital Discharge Register data and analyzed according to ICD-10 chapters. Results: 10.7% of women continued to smoke after the first trimester. After adjusting for confounding factors women in both smoking groups had more hospital treatment compared with nonsmokers. Especially outpatient treatment was more common among mothers who continued to smoke compared to those who quit smoking in the first trimester in several ICD-10 chapters. Compared to non-smokers, aOR for mental and behavioral disorders (F00–F99) was 2.14 (95% confidence interval 2.00–2.30) in the quit smoking group and 3.88 (3.71–4.06) in the continued smoking group. Similarly, aOR for respiratory diseases (J00–J99) was 1.26 (1.15–1.39) and 1.61 (1.52–1.71), respectively and aOR for genitourinary diseases (N00–N99) was 1.10 (1.03–1.17) and 1.29 (1.23–1.35), respectively. Some similar findings were made also in inpatient care. Some similar findings were made also in inpatient care. Conclusions: Women who smoke during pregnancy seem to require more hospital care for various reasons. These findings emphasize the importance of actions for smoking cessation during pregnancy and women should be encouraged to quit as early as possible. Implications: Maternal smoking during pregnancy is associated with greater rates of both outpatient and inpatient hospital care during pregnancy. Women who quit smoking had a similar risk for hospital care during pregnancy with nonsmokers in certain diagnosis chapters, which is very motivational and could be used as an informational tool in prenatal clinics to encourage smoking cessation as it is never too late to quit smoking during pregnancy.